Climatic Influence on Slope Failure: A Case Study at Kem Terendak, Melaka - Lias, Raazlizam; Mohamed Jais, Ismacahyadi Bagus; Che Lat, Diana (International Journal of Sustainable Construction Engineering and Technology, 2022)
Slope failure or landslide is always ascribing to the slope sculptures in the hilly area. The trend of people building a structure on a hilly area has resulted in slope cutting works being carried out aggressively and, at the same time, has increased the risk of landslides. Most of the community lacks understanding regarding slope care and maintenance, which adds to the slope suffering. One of the factors contributing to slope failure is rainfall. The rainfall-runoff to the slope erodes the turfed and topsoil particles from the slope surface. When the slope surface is exposing to extreme weather, then the slope failure will occur. These failures pose a significant engineering hazard, necessitating urgent repair work and planning in many areas. All failures that occur will require expensive repairing costs. Therefore, this study is carried out to model the rainfall-induced slope failure occurrence at Kem Terendak, Melaka. This study utilises a simulation of slope stability analysis by limit equilibrium, Slope/W 2012 and finite element software for simulating groundwater flow in saturated steady-state situations, Seep/W 2012 in order to analyse the stability of the slope with the influence of climate. Through those analysis, one can understand the causes and mechanisms of the landslide. At the same time, the factors that influence the occurrence of failures can be identified and appropriate action can be taken to reduce or even eliminate the root cause of slope failures. In addition, effective and efficient slope repair methods can be proposed with optimal cost.